Persistent burden and health inequalities of disease in women of childbearing age attributable to Intimate Partner Violence, 1990–2021 - Song, Yingda; Wang, Juan; Wang, Jiaxuan; Ren, Yan; Ma, Jun (Frontiers in Psychiatry, 2025)
AimsIntimate Partner Violence (IPV) presents a significant global public health issue, particularly affecting women of childbearing age (WBCA). The COVID-19 pandemic has exacerbated the IPV globally. This study aimed to assess the global burden and health inequalities attributable to IPV among WBCA from 1990 to 2021.MethodsWe utilized data from the Global Burden of Disease (GBD) 2021 to assess the disease burden attributable to IPV among WBCA, by age group, GBD region, and country, measured using mortality, disability-adjusted life years (DALYs), age-standardized mortality rate (ASMR), and age-standardized DALY rate (ASDR). Joinpoint regression was utilized to examine trends over time. To assess both absolute and relative health disparities, the Slope Index of Inequality (SII) and the Concentration Index were computed.ResultsIn 2021, global IPV-related mortality and DALYs among WBCA were 44,661 and 5.35 million, respectively. The IPV-attributable ASDR declined from 292.88 per 100,000 population in 1990 (95% uncertainty interval [UI]: 167.98 to 439.65) to 272.08 per 100,000 population in 2021 (95% UI: 148.65 to 422.82), with average annual percentage change (AAPC) of -0.19 (95% confidence interval [CI]: -0.39 to -0.10). Significant inflection points were identified in the years 2000 and 2019. In 2019, the IPV-attributable ASDR began to rise. This upward trend was primarily driven by IPV-related depressive disorders burden. The IPV-attributable ASMR decreased from 2.61 per 100,000 population in 1990 (95% UI: 1.73 to 3.71) to 2.26 per 100,000 population in 2021 (95% UI: 1.45 to 3.21), with AAPC of -0.46 (95% CI: -0.60 to -0.33). This downward trend was also observed in the burden caused by IPV-related HIV/AIDS and interpersonal violence. In 2021, the highest disease burden attributable to IPV was reported among the 30–34 age group, low and low-middle Socio-Demographic Index (SDI) regions, and Eastern Sub-Saharan Africa. The largest increase in disease burden attributable to IPV occurred in the 40–44 age group, Oceania, and low-middle SDI region. The absolute value of the SII for ASMR increased from 2.04 in 1990 to 4.59 in 2021, while that of the SII for ASDR decreased from 321 in 1990 to 190 in 2021. The relative Concentration Index for ASMR and ASDR dropped from -0.33 and -0.2 in 1990 to -0.46 and -0.26 in 2021, respectively. The worsening of health inequalities was mainly concentrated in low- and middle-income countries (LMICs) and IPV-related HIV/AIDS burden.ConclusionsSince 1990, the burden attributable to IPV among WBCA has generally declined. However, the COVID-19 pandemic reversed this trend, particularly in IPV-related depressive disorders burden. Health inequalities have worsened, particularly in relation to IPV-related HIV/AIDS burden. Increased attention must be given to eliminating the preventable burden of IPV in LMICs, with coordinated global efforts required to mitigate its health impact.